One leg lateral jumps - A new test for team players evaluation - Taboga, P.; Sepulcri, L.; Lazzer, S.; de Conti, D.; Di Prampero, P. E. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: We assessed the subject`s capacity to accelerate himself laterally in monopodalic support, a crucial ability in several team sports, on 22 athletes, during series of 10 subsequent jumps, between two force platforms at predetermined distance. Methods: Vertical and horizontal accelerations of the Centre of Mass (CM), contact and flight times were measured by means of force platforms and the Optojump-System®. Individual mean horizontal and vertical powers and their sum (total power) ranged between 7 and 14.5 W/kg. "Push angle", i.e., the angle with the horizontal along which the vectorial sum of all forces is aligned, was calculated from the ratio between vertical and horizontal accelerations: it varied between 38.7 and 49.4 deg and was taken to express the subject technical ability. Results: The horizontal acceleration of CM, indirectly estimated as a function of subject`s mass, contact and flight times, was essentially equal to that obtained from force platforms data. Since the vertical displacement can be easily obtained from flight and contact times, this allowed us to assess the Push angle from Optojump data only. Conclusions: The power developed during a standard vertical jump was rather highly correlated with that developed during the lateral jumps for right (R=0.80, N.=12) and left limb (R=0.72, N.=12), but not with the push angle for right (R=0.31, N.=12) and left limb (R=-0.43, N.=12). Hence standard tests cannot be utilised to assess technical ability. Lateral jumps test allows the coach to evaluate separately maximal muscular power and technical ability of the athlete, thus appropriately directing the training program: the optimum, for a team-sport player being high power and low push-angle, that is: being "powerful" and "efficient".